Iodine Biofortification Counters Micronutrient Deficiency and Improve Functional Quality of Open Field Grown Curly Endive - Leo Sabatino; Francesca Di Gaudio; Beppe Benedetto Consentino; Youssef Rouphael; Christophe El-Nakhel; Salvatore La Bella; Sonya Vasto; Rosario Paolo Mauro; Fabio D’Anna; Giovanni Iapichino; Rosalia Caldarella; Claudio De Pasquale (Horticulturae, 2021)
Human iodine (I) shortage disorders are documented as an imperative world-wide health issue for a great number of people. The World Health Organization (WHO) recommends I consumption through ingestion of seafood and biofortified food such as vegetables. The current work was carried out to appraise the effects of different I concentrations (0, 50, 250, and 500 mg L−1), supplied via foliar spray on curly endive grown in the fall or spring–summer season. Head fresh weight, stem diameter, head height, and soluble solid content (SSC) were negatively correlated to I dosage. The highest head dry matter content was recorded in plants supplied with 250 mg I L−1, both in the fall and spring–summer season, and in those cultivated in the fall season and supplied with 50 mg I L−1. The highest ascorbic acid concentration was recorded in plants cultivated in the spring–summer season and biofortified with the highest I dosage. The highest fructose and glucose concentrations in leaf tissues were obtained in plants cultivated in the spring–summer season and treated with 250 mg I L−1. Plants sprayed with 250 mg I L−1 and cultivated in the fall season had the highest I leaf concentration. Overall, our results evidently suggested that an I application of 250 mg L−1 in both growing seasons effectively enhanced plant quality and functional parameters in curly endive plants.